Did Trump's Trade War Impact the 2018 Election? - Emily Blanchard; Chad P. Bown; Davin Chor (Center for Economic Studies and Ifo Institute (CESifo), 2020)
We find that Republican candidates lost support in the 2018 congressional election in counties more exposed to trade retaliation, but saw no commensurate electoral gains from US tariff protection. The electoral losses were driven by retaliatory tariffs on agricultural products, and were only partially mitigated by the US agricultural subsidies announced in summer 2018. Republicans also fared worse in counties that had seen recent gains in health insurance coverage, affirming the importance of health care as an election issue. A counterfactual calculation suggests that the trade war (respectively, health care) can account for five (eight) of Republicans' lost House seats.
Keywords: F13; F14; 330; trade war; trade policy; retaliatory tariffs; agricultural subsidies; health insurance coverage; voting